Association of polymorphous light eruption with NOD-2 and TLR-5 gene polymorphisms - Kurz, B.; Arndt, S.; Unger, P.; Ivanova, I.; Berneburg, M.; Hellerbrand, Claus; Karrer, S. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background: Polymorphous light eruption (PLE) is a common, immunologically mediated, photosensitive skin disease. After ultraviolet-B (UV-B) irradiation, patients with PLE show reduced Langerhans cell (LC) depletion in the epidermis, which results in a non-suppressive microenvironment in the skin. Interestingly, severe acute graft-versus-host disease (aGvHD) occurred in stem cell transplanted patients that showed no or incomplete depletion of LCs after UVB irradiation. Genetic variation in nucleotide-binding oligomerization domain 2 (NOD-2) and toll-like receptor 5 (TLR-5) genes also confers susceptibility to aGvHD. Objectives: We hypothesized that PLE is associated with genetic variation in the NOD-2 and TLR-5 genes. Methods: We investigated single-nucleotid polymorphisms (SNPs) of NOD-2 (R702W, G908R, 3020Cins) and TLR-5 (A592S, P616L, N392STOP) in skin biopsies of patients with PLE (n = 143) and in healthy controls (n = 104) using restriction fragment length polymorphism analysis. Results: The frequency of NOD-2 alleles with the SNP R702W was significantly higher in PLE than in controls (31.8% vs. 6.3%; P < 0.0001), and homozygous carriers of this mutation were more common in PLE (27.9% vs. 0%; P < 0.0001). For SNP 3020Cins, the allele frequency (7.3% vs. 0.7%; P = 0.0025) and the number of heterozygotes (14.7% vs. 1.3%; P = 0.0019) were higher in PLE. The frequency of alleles with the N392STOP SNP of the TLR5 gene, which is associated with a truncated, non-functional receptor, was significantly higher in PLE (21% vs. 5%; 7% vs. 1% homozygotes, 28% vs. 8% heterozygotes; P < 0.0001). The other SNPs did not differ significantly. Conclusions: This study yielded a high frequency of functional SNPs in the NOD-2 and TLR-5 genes in PLE. The same SNPs are associated with aGvHD and there are similarities in the reaction of LCs after UVB irradiation between aGvHD and PLE. This leads to the hypothesis that patients with PLE may be more susceptible to developing GvHD after stem cell transplantation, an assumption that needs to be investigated further.
CRIS-Team Scopus Importer:2022-07-15